Students’ Mathematical Problem Solving Ability Reviewed from Adversity Quotient: Systematic Literature Review - Lestari, Ika Dhian; Juandi, Dadang (Universitas Sebelas Maret, 2023)
The purpose of this study is to explain the findings of a study on students' mathematical problem-solving abilities, which were examined using the Adversity Quotient (AQ) type. This study uses the Systematic Literature Review (SLR) method with the PRISMA protocol for all research articles indexed on Google Scholar, Garuda, ERIC, and Semantic. The sample in this study consisted of 29 publications about students' mathematical problem-solving abilities that were reviewed using the Adversity Quotient (AQ) and were published between 2018 and January 2023 in Indonesia. The findings of this study will be evaluated based on the year of publication, education level, research location, selected material, problem-solving phases used, and the AQ-based description of students' mathematical problem-solving ability. Using the SLR method, it was discovered that research on students' mathematical problem-solving abilities in terms of AQ type received a lot of attention each year, with the majority of this research being conducted at the junior high school education level with the Polya stage on the topic of algebra and on the island of Java. Furthermore, it was discovered that AQ effects students' characteristics in terms of mathematical problem solving abilities qualitatively by synthesizing the results of study on students' mathematical problem solving abilities in terms of AQ type.